In vitro prediction of Vallisneria americana Michx. stress by enrichment of ammonium and nitrate ions - Ruiz Carrera, Violeta; Sánchez, Alberto J.; Contreras-Sánchez, Wilfrido M; Salcedo-Meza, Miguel A (Ecosistemas y Recursos Agropecuarios, 2021)
Nutrient enrichment is an environmental stress factor involved in the decline of submerged vegetation. However, the physiological or toxicological sensitivity of the genotypes varies due to microbiotic interactions and physicochemical imbalance of water, which have been studied through a reductionist approach and controlled experiments. The objective of the study was to evaluate, in an in vitro culture model of Vallisneria americana, the increase of different sources and concentrations of N on the survival and growth of leaves and roots. Juvenile plants in vitro grew at concentrations of 500 to 2 000 µg L−1 of total N with sources of NH4, NO3 and NH4:NO3 (1:1) in a factorial design 4 x 3, in short- and medium-term evaluations. Survival was inversely proportional to symptoms of chlorosis, necrosis, or tissue rupture. The first foliar elongation was measured with a non-destructive method. While at 25 days, the individual and average length of leaves and roots, number of regenerated leaves and number of total roots were quantified. The plants did not show symptoms of vulnerability. NH4 in all its concentrations inhibited the growth of the nine parameters analyzed. In contrast, NH4:NO3 caused two inhibitions at the leaf level and NO3 stimulated leaf and root growth. The growth prediction proved promising to discriminate stress factors on the submerged vegetation of the Pantanos de Centla.